The Magnitude of Surface Ocean Acidification and Carbon Release During Eocene Thermal Maximum 2 (ETM-2) and the Paleocene-Eocene Thermal Maximum (PETM) - Harper, D. T.; Honisch, B.; Zeebe, R. E.; Shaffer, G.; Haynes, L. L.; Thomas, E.; Zachos, J. C. (My University, 2020)
Eocene Thermal Maximum 2 (ETM-2; 54.1 Ma) was the second largest Eocene hyperthermal. Like the Paleocene-Eocene Thermal Maximum (PETM), ETM-2 was characterized by massive carbon emissions and several degrees of global warming and thus can serve as a case study for assessing the impacts of rapid CO2 emissions on ocean carbonate chemistry, biota, and climate. Marine carbonate records of ETM-2 are better preserved than those of the PETM due to more subdued carbonate dissolution. As yet, however, the magnitude of this carbon cycle perturbation has not been well constrained. Here, we present the first records of surface ocean acidification for ETM-2, based on stable boron isotope records in mixed-layer planktic foraminifera from two midlatitude ODP sites (1210 in the North Pacific and 1265 in the SE Atlantic), which indicate conservative minimum global sea surface acidification of -0.20 +0.12/-0.13 pH units. Using these estimates of pH and temperature as constraints on carbon cycle model simulations, we conclude that the total mass of C, released over a period of 15 to 25 kyr during ETM-2, likely ranged from 2,600 to 3,800 Gt C, which is greater than previously estimated on the basis of other observations (i.e., stable carbon isotopes and carbonate compensation depth) alone.
Keywords: boron isotope; carbon isotope; etm-2; hyperthermal; ocean acidification; petm